Beef Cattle Business in Dry Land Area Parangloe District Gowa - Supardi Rusdiana; Soeharsono Soeharsono; Teuku Reza Ferasyi (The International Journal of Tropical Veterinary and Biomedical Research, 2017)
The study was conducted in the village Payangkalang Parangloe District of Gowa in South Sulawesi in 2017, with the field survey method Substance himself to Bali beef cattle breeders, through interviews and questionnaires to 18 farmers, by the way (sample random sampling). Respondents beef cattle breeders, classified into 2 (two) business model with a scale of 2 adult males and 3 females scale adult stem, this data will be analyzed using economic analysis of income B/C. Based on the information that the beef cattle population of Bali is quite a many, so that the criterion for consideration for the study area. Beside that all cattle breeders Bali is already a member of a group of farmers. The results showed that net profit in the maintenance of Bali beef cattle female parent of $13.381.250/year with  B/C ratio of 1.2 and a gain on the maintenance of male cattle Bali for $ 3.881.250 year, with B/C ratio of 1.1. To maintain a profitable cattle faremr cows, while the majority of beef cattle Bali parent can still be maintained as an investment for the procreation of children next year.